Emotion in Scholarly Discourse: Denial, Deconstruction, Reinstatement - Bennett, Karen (2012)
Since the 17th century, a battle has been raging between two distinct paradigms of knowledge in which the role of emotion has taken centre stage. With the Scientific Revolution and Enlightenment, all forms of subjectivity were effectively proscribed, a philosophical orientation that was reflected in the lexico-grammar of scholarly discourse. However, despite the increasing centrality of the scientific paradigm in the modern world, the older humanities tradition has continued to make its presence felt over the years, not least through the challenges to objectivity raised by poststructuralism. This paper traces the various phases of this battle in England and Continental Europe. It looks at how the humanities paradigm flourished in Catholic Europe long after Scholasticism and Rhetoric had been discredited in Protestant England, and focuses on various historical moments when the two paradigms came into conflict.